Acupuncture’s Effect of PC6, LV3 Combined with YNSA in Essential Hypertension Cases (ICD 10: I10) Grade I,II - Widowati, Risna; Faricha Indra Hapsari; Sumanto (Indonesian Journal of Acupuncture, 2024)
Hypertension is the second highest cause of death in Indonesia (25.8%) in outpatients. Acupuncture has been used to treat various diseases including hypertension. The purpose of this study was to determine the acupuncture’s effect of PC6 and LV3 combined with YNSA Ypsilon HT and LV points in cases of essential hypertension (ICD 10: I10) grade I, II. The study was conducted in Ngargorejo, Ngemplak, Boyolali from October 2018 to March 2019 using a design (RCT) or randomized experiment with 33 subjects, divided into experimental groups (17 people) and control groups (16 people) with SRS  as a sampling technique. Mann-Whitney obtained p <0.05, which means that there was an acupuncture effect of PC6 and LV3 combined with YNSA Ypsilon HT and LV on blood pressure reduction. The systolic pressure was p <0.05 and the diastolic pressure was p> 0.05 in the control group. While the experimental group's systolic and diastolic pressures were p <0.05. It can conclude that PC6 and LV3 combined with YNSA Ypsilon HT and LV points had more effect on systolic and diastolic pressure reduction than sham acupuncture which only affected systolic pressure reduction with short-term effects.